2010
DOI: 10.1128/jvi.00443-10
|View full text |Cite
|
Sign up to set email alerts
|

Virus Cell-to-Cell Transmission

Abstract: 2Viral infections spread based on the ability of viruses to overcome multiple barriers and move from cell to cell, tissue to tissue, and person to person and even across species. While there are fundamental differences between these types of transmissions, it has emerged that the ability of viruses to utilize and manipulate cell-cell contact contributes to the success of viral infections. Central to the excitement in the field of virus cell-to-cell transmission is the idea that cell-to-cell spread is more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
267
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(285 citation statements)
references
References 139 publications
11
267
2
1
Order By: Relevance
“…Alternatively, the LCMV-G protein, but not RABV-G protein, might enable a phenomenon known as transcytosis. HIV, which is also an enveloped virus, can pass from a cell to its neighbor by using such a mechanism (37,38). Based on these results from CP injections, replication-incompetent VSV pseudotyped with LCMV-G could thus be explored for use as a monosynaptic tracer, even without the engineering discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the LCMV-G protein, but not RABV-G protein, might enable a phenomenon known as transcytosis. HIV, which is also an enveloped virus, can pass from a cell to its neighbor by using such a mechanism (37,38). Based on these results from CP injections, replication-incompetent VSV pseudotyped with LCMV-G could thus be explored for use as a monosynaptic tracer, even without the engineering discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the human immunodeficiency virus (HIV) and the human T cell lymphoma virus these cell-cell contacts share features with immunological synapses and have been designated infectious or virological synapses (13,14,19,29,41). Using the murine leukemia virus (MLV) as a model system, we demonstrated that the interaction between the viral Env glycoprotein (Env), expressed on the infected cell and the viral receptor, expressed on the uninfected target cell, leads to the establishment of cell-cell contacts (32,45). Importantly, following the establishment of cellcell adhesion, assembly was polarized toward the cell-cell contact (16).…”
mentioning
confidence: 99%
“…Viruses exploit and manipulate cell-cell contacts for efficient spreading (12,18,32,37,43). In the case of the human immunodeficiency virus (HIV) and the human T cell lymphoma virus these cell-cell contacts share features with immunological synapses and have been designated infectious or virological synapses (13,14,19,29,41).…”
mentioning
confidence: 99%
“…After this initial event, infection can spread either locally or across long distances via hematogenous, lymphatic, or neural routes. In either case, spread from cell to cell often involves direct transmission of infectious particles with no or limited release of infectious particles into the extracellular milieu (1). Cell-to-cell spread of some infections, such as HIV, involves transfer of many viral particles (2), whereas other infections, such those caused by poliovirus, involve transfer of small numbers of particles (3).…”
mentioning
confidence: 99%